2013
DOI: 10.3892/ijo.2013.1816
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of volatile oil from Pyrolae herba and antiproliferative activity against SW1353 human chondrosarcoma cells

Abstract: Abstract. The objective of the present study was to identify chemical constituents of volatile oil from Pyrolae herba (PHVO) and evaluate the antiproliferative activity of PHVO against SW1353 human chondrosarcoma cells. The volatile oil from Pyrolae herba was prepared by hydrodistillation and characterized by gas chromatography-mass spectroscopy (GC-MS). A total of 12 components in PHVO were identified representing 81.62% of the total integrated chromatographic peaks. The major compounds were found to be n-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As p21 is negative regulator of G 1 phase transition, increased expression of this protein by the action of patchouli alcohol is indicative of cell cycle inhibition [65]. Similar arresting of the G 1 transition has also been reported in different types of cancer in response to various other EOs [66, 67]. EOs of Curcuma wenyujin inhibit S/G 2 phase transition leading to cancer cell death [68].…”
Section: Mechanism Of Action Of Eosmentioning
confidence: 89%
“…As p21 is negative regulator of G 1 phase transition, increased expression of this protein by the action of patchouli alcohol is indicative of cell cycle inhibition [65]. Similar arresting of the G 1 transition has also been reported in different types of cancer in response to various other EOs [66, 67]. EOs of Curcuma wenyujin inhibit S/G 2 phase transition leading to cancer cell death [68].…”
Section: Mechanism Of Action Of Eosmentioning
confidence: 89%
“…In folk medicine, essential oil constituents from plants are used as alternative treatments for a wide range of illnesses including cancer prevention and treatment [7][9]. Recently, studies have reported that essential oils, including the leaf of Porcelia macrocarpa [10] and Pyrolae herba [11], the heartwood of Cunninghamia lanceolata var. konishii [12], and the seed of Litsea cubeba [13], possess anticancer effects against different types of human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Hexanal, benzaldehyde, 2‐pentylfuran, naphthalene and 6,10,14‐trimethyl‐2‐pentadecanone were present at the highest level in all porridge of the quinoa varieties. The later is involved in the synthesis of vitamin E, and has been detected in several medicinal plants as one of the main compounds with antimicrobial and antioxidant function . It is a non‐aromatic compound with a slight fatty aroma, and so it might be one of the important volatile compounds in the quinoa porridge.…”
Section: Resultsmentioning
confidence: 99%
“…The later is involved in the synthesis of vitamin E, and has been detected in several medicinal plants as one of the main compounds with antimicrobial and antioxidant function. 15,30,31 It is a non-aromatic compound with a slight fatty aroma, and so it might be one of the important volatile compounds in the quinoa porridge. Further investigation of the role of some of these compounds in quinoa porridge, paying…”
Section: Cluster Analysis Of Volatile Compoundsmentioning
confidence: 99%